O uso de sensoriamento remoto como recurso pedagógico para o estudo de geometria plana e espacial alavancada pela metodologia webquest - Saavedra, Marta Martilene Rodrigues Ribeiro (2012)
The present work has its theory based on the mathematic study coupled with the information technology and geo-technology. The methodology used was the Webquest named The shapes of the city of Santa Maria designed and implemented by the researcher. This methodology verifies the contribution of the remote sensing as a pedagogical resource in the teaching of mathematics, specifically on the plane and spatial geometry contents, proposed in the elementary school program. The pedagogical experiment was developed in the 4° and 8° grades of an elementary municipal school. To this study it was considered the particularities of an action research model following the parameters of a qualitative research. The data was collected through participant observation, individual interview with the students of the 4° grade, by a questionnaire with open questions directed to the 8° grade students and a documental analysis of the production of the students. The activities were considered innovative and interesting by the authors involved (teachers and students) drawing attention to the research and the realization of tasks, as well as, allowing the construction of the multidisciplinary knowledge in a pleasant way.